The prevalence of Pseudomonas aeruginosa and multidrug resistant Pseudomonas aeruginosa in healthy captive ophidian - Sala, Andrea (PeerJ, 2019)
BACKGROUND: Snakes are globally considered as pet animals, and millions of ophidians are bred in captivity. Pseudomonas aeruginosa is a ubiquitous Gram-negative bacterium that can act as an opportunistic pathogen of man and animals and is frequently present in the oral and cloacal microbiota of healthy ophidians. It can cause severe clinical diseases and often shows antibiotic resistance. The aim of this study was to evaluate the prevalence and antibiotic resistance profiles of P. aeruginosa isolated from the cloacal microbiota of a large population sample of healthy captive ophidians and to evaluate the statistical associations with farming conditions. METHODS: A total of 419 cloacal swabs were collected from snakes belonging to the Boidae (n = 45), Colubridae (n = 48) and Pythonidae (n = 326) families and inoculated onto complete culture media. Food, water and bedding samples were also analyzed. The antimicrobial susceptibility of P. aeruginosa isolates was evaluated through the Kirby-Bauer agar diffusion test. Statistical analyses were performed with the chi-square test. RESULTS: The prevalence of P. aeruginosa was 59.9%, and 35.5% of these strains were multidrug resistant (MDR). The prevalence of MDR P. aeruginosa was significantly higher in adult samples than in young samples, and widespread resistance to Cephalosporins, Polymyxins and Sulfonamides was observed. Statistically significant differences in the prevalence of P. aeruginosa were observed depending on the farm size and snake family. Feeding thawed prey was associated with a higher P. aeruginosa and MDR P. aeruginosa prevalence. Moreover, snakes fed home-raised prey had a significantly higher MDR P. aeruginosa prevalence than snakes fed commercially available feed. Less frequent terrarium cleaning was associated with a higher MDR P. aeruginosa prevalence. On the other hand, snake reproductive status was not significantly associated with P. aeruginosa or MDR P. aeruginosa prevalence. All food, water and bedding samples were negative for P. aeruginosa presence. DISCUSSION: The overall P. aeruginosa prevalence found in this study was lower than that found by other authors, but a high proportion of the isolates were MDR. This study highlighted the presence of constitutive (such as age and taxonomic family) and managerial (farm size, cleaning cycle frequency and food type) factors associated with P. aeruginosa and/or MDR P. aeruginosa prevalence. Good breeding management and proper antibiotic treatment of P. aeruginosa infections could help reduce the presence of P. aeruginosa and MDR P. aeruginosa in the gut microbiota of snakes and consequently reduce the risk to public health.